Penerapan Sistem Inferensi Fuzzy Metode Mamdani Untuk Penentuan Konsentrasi Mahasiswa Teknik Informatika - S, Richasanty Septima; Syahputra, Hendri; Zulfa, Ira; Gemasih, Husna; Nurdin, N (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
The Informatics Engineering study at Gajah Putih University it self has two concentrations, namely intelligent computing and computer networking. Confusion problems arise or most of the students’s mistakes regarding specializationa are in accordance with abilities because the many elective courses offered are in line with the interests offered and also the inability of students to calculate the value of previous basic courses. So based on this proble, decision-making aids or recommendations are needed to students about which major concentration is most appropriate according to their abilities. The author proposes system that is able to solve the problems above, namely by creating a system based on a fuzzy inference system with the mamdani method. Mamdani’s Fuzzy Inference System (FIS) or often also known as the max-min method is used because it can tolerate uncertainty values and is based on reasoning that uses an uncertainty approach that combines numerical variables, linguistic variables and rules. In addition, the Mamdani Fuzzy Inference System (FIS) is also used because it has a smaller error value comared to the logic method. This research produced a system for determining the concentration of majors in the informatics engineering study program to help determine the appropriate recommendations with a range of defuzzilication values, namely the lowest value of 4.14 and highest 4.41.